Preparation and characterization of nanocomposite textile filter for separation of the oil/water mixture using PA-PVA blends reinforced with carbon nanoparticles - Rusul Mohamed Darweesh; Balqees Mohamed Al-dabbag; Hanaa Jawad Kadhim (مجلة بغداد للعلوم, 2024)
The electrospinning technique used to prepare a nano fibre filter under limited conditions involves (20 kV applied voltage, 15 cm gap distance, 1 ml/h:  flow rate, and 0.4 mm needle diameter). Several tests for prepared materials were conducted including [scanning electron microscopy (SEM-EDX), Fourier Transform Infrared (FTIR), contact angle, and particle size analysis]. As well as, the characterization of the water/oil mixture was tested before the filtration process and after it. According to the SEM data, smooth and homogeneous nanofibers with an approximate diameter of 350 nm and open porosity morphology were produced using the electrospinning approach. The liquid particles adhere to the filter fibers and work to shrink the holes in the filter, allowing the water to pass through the filter while recovering its characteristics, according to SEM results obtained after the filtration process.     According to AFM data, the majority of pores have a diameter of around 100 nm, while the minority has a diameter of more than 100 nm but less than 2500 nm.  The results of the catachrestic of water were saved after filtration of a sample by the prepared filter and it closed up the normal water properties by increasing the carbon nanoparticles ratios. The infrared data (FTIR) demonstrate that there is a physical interaction between the polymeric fibers and the added carbon particles since there is a drop in the intensity of infrared radiation after the carbon particles are added to the filter fibers. The hydrophilicity property is found to rise with increasing carbon nanoparticle ratio, and contact angle data demonstrate that this characteristic reduces with increasing carbon nanoparticle ratio, going from 72 o for pure nano filter to 44 o for filter with 0.3 percentage of carbon nanoparticles.